2004
DOI: 10.1590/s0102-311x2004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre hábitos bucais, alterações oronasofaringianas e mal-oclusões em pré-escolares de Vitória, Espírito Santo, Brasil

Abstract: The objective of this study was to estimate the prevalence of malocclusion and associated variables such as deleterious habits (DH) and oronasopharyngeal alterations (OA), mouth breathing, atypical phonation, and atypical swallowing in three-year-old children in Vitória, Espírito Santo State, Brazil. The sample included 291 children of both sexes enrolled in a Children's Educational Center and selected through probability sampling by conglomerates. Logistic regression indicated a high relative risk (RR) in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
37

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 18 publications
2
6
0
37
Order By: Relevance
“…8 These lower prevalence should be attributed to the lower incidence of deleterious sucking habits in the Japanese ethnic group previously discussed, which some authors 5,19,20 believe The results of the present study showed statistically significant association (p=0.000) between the finger/pacifier sucking and anterior open bite (Tables 3 and 4) corroborating previous studies. 3,4,8,13,16,20,22 The relative risk observed for anterior open bite in children with deleterious sucking habits was 10 times higher (p=10.77) than those who did not have this behavior. Serra-Negra, Pordeus and Rocha Jr. 16 found a risk close to that (O.R.=14.1).…”
Section: Discussionmentioning
confidence: 93%
“…8 These lower prevalence should be attributed to the lower incidence of deleterious sucking habits in the Japanese ethnic group previously discussed, which some authors 5,19,20 believe The results of the present study showed statistically significant association (p=0.000) between the finger/pacifier sucking and anterior open bite (Tables 3 and 4) corroborating previous studies. 3,4,8,13,16,20,22 The relative risk observed for anterior open bite in children with deleterious sucking habits was 10 times higher (p=10.77) than those who did not have this behavior. Serra-Negra, Pordeus and Rocha Jr. 16 found a risk close to that (O.R.=14.1).…”
Section: Discussionmentioning
confidence: 93%
“…Algumas pesquisas realizadas no Brasil têm ressaltado a alta prevalência de más oclusões entre a população de crianças, na fase de dentição decídua, com valores superiores a 70% 7,16,17 . Porém, outros estudos 18,19 mostram uma tendência semelhante à encontrada neste trabalho, em que 53,2% da amostra apresentaram algum tipo de má oclusão.…”
Section: Resultsunclassified
“…Isso porque a chupeta produz no organismo uma saciedade sensorial proporcionada pelo estímu-lo à sucção, salivação e deglutição, saturando de informações aferentes o sistema funcional da alimentação e competindo com a amamentação. 23 A sucção de chupeta surge como fator de risco para a perda do vedamento labial com o tempo prolongado de uso, em torno de oito meses, e, com o passar do tempo, assume-se como o mais importante fator de risco, por volta dos 16 meses. Segundo Praetzel 24 , o uso de chupeta pode levar uma criança a ser um respirador bucal habitual, devido à compensação postural adquirida pela musculatura facial e da língua e pela mandíbula (boca aberta, hipotonicidade da musculatura facial e da lín-gua), necessária para manter tal objeto na boca.…”
Section: Discussionunclassified